2022
DOI: 10.3390/bdcc7010002
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Maturity Assessment Models: A Systematic Literature Review

Abstract: Big Data and analytics have become essential factors in managing the COVID-19 pandemic. As no company can escape the effects of the pandemic, mature Big Data and analytics practices are essential for successful decision-making insights and keeping pace with a changing and unpredictable marketplace. The ability to be successful in Big Data projects is related to the organization’s maturity level. The maturity model is a tool that could be applied to assess the maturity level across specific key dimensions, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…After validating the model and finalizing the components, the assessment tool was built and used to evaluate the city's level of maturity [42]. Each level within a focus area had three checkpoints: questions that can be answered by "yes" or "no" to assess the current situation [28,38].…”
Section: Building the Assessment Toolmentioning
confidence: 99%
“…After validating the model and finalizing the components, the assessment tool was built and used to evaluate the city's level of maturity [42]. Each level within a focus area had three checkpoints: questions that can be answered by "yes" or "no" to assess the current situation [28,38].…”
Section: Building the Assessment Toolmentioning
confidence: 99%
“…Similarly, Saleh and Ijab (2023) examined Fourth Industrial Revolution maturity and identified readiness factors: infrastructure, regulatory, skills and competency, technology and commitment. In contrast, Al-Sai et al (2022) specifically focused on big data analytics maturity models highlighting that due to the importance of big data maturity, additional research is required to investigate and provide more details about the assessment dimensions toward developing a new maturity assessment model for big data maturity. In addition, Giang and Liaw (2022) applied a dynamic approach for predicting SME big data analytics readiness using Chi-square automatic interaction detection (CHAID), Bayesian network, neural network, and C5.0 algorithms of data mining.…”
Section: Introductionmentioning
confidence: 99%